The Psychological Impact of the COVID-19 Epidemic on Guangdong College Students: The Difference Between Seeking and Not Seeking Psychological Help - Liang, Shun-Wei; Chen, Rong-Ning; Liu, Li-Li; Li, Xue-Guo; Chen, Jian-Bin; Tang, Si-Yao; Zhao, Jing-Bo (Frontiers in Psychology, 2020)
Background: Coronavirus disease 2019 (COVID-19) has considerably psychologically impacted Chinese college students. Several types of online mental health services were widely implemented for college students during the outbreak. This study investigated the relationship between college students' mental health status and psychological help-seeking behaviour to test the phases-decision-making model (PDM). Methods: A cross-sectional survey was conducted among college students in Guangdong Province using an online platform. In total, 4,164 students were assigned to the ‘counselling group’ or ‘non-counselling group’ according to whether they had sought psychological help because of the COVID-19 outbreak; the groups were matched based on age, sex and grade. Demographics, perceived mental health and experience with seeking psychological help were recorded. Fear, depression and trauma, were assessed by the COVID-19 Fear Screening Scale, Patient Health Questionnaire and Impact of Event Scale-6. Results: The fear, depression and trauma scores were significantly higher in the counselling group than in the non-counselling group (Ps<0.001). Fear (OR=1.27, p<0.001), depression (OR=1.02, p=0.032), trauma (OR=1.08, p<0.001), poor perceived mental health status (OR=3.61, p=0.001) and experience with seeking psychological help (OR=7.06, p<0.001) increased the odds of seeking psychological help. Conclusion: During the COVID-19 epidemic, the rate of psychological help-seeking was still low, and college students in poor psychological condition sought psychological counselling more. Fear, depression, trauma, experience with seeking psychological help and perceived mental health can effectively predict psychological help-seeking behaviour. These findings emphasized the importance of closely monitoring college students’ psychological status, providing psychological intervention, and improving the probability of seeking psychological help.